The purification and characterization of acetoacetyl-coenzyme A reductase from Azotobacter beijerinckii - Ritchie, G. A. F. (1971)
A soluble acetoacetyl-CoA reductase (EC 1.1.1.36) was purified 54-fold from Azotobacter beijerinckii N.C.I.B. 9067 and the reaction product identified as d(−)-β-hydroxybutyryl-CoA. The Michaelis constants for acetoacetyl-CoA, NADPH and NADH were determined and the reaction rate was found to be some fivefold greater with NADPH than with NADH. At neutral pH the equilibrium greatly favours the formation of the reduced product. Substrate specificity was in the order: acetoacetyl-CoA>acetoacetylpantetheine>acetoacetyl-(acyl-carrier protein). The enzyme possesses a functional thiol group, suffers inactivation by oxygen and is inhibited by thiol-blocking reagents. Inhibition by p-chloromercuribenzoate is reversed by excess of dithiothreitol, which also protects the enzyme from inactivation by oxygen.